ChemInform Abstract: A New Approach to the Synthesis of (Z)‐2‐Fluoro‐2‐alkenals via Wittig‐Type Carbonyl Condensation Reactions of 2‐(Fluoromethyl)‐4, 4, 6‐trimethyl‐1, 3‐oxazine Phosphonium Bromide. Issue 27 (13th June 2013) - Kajjout, Mohammed; Smietana, Michael; Leroy, Jacques; Rolando, Christian
Abstract Condensation of phosphonium bromide (I) with aldehydes gives (E/Z)‐mixtures of alkenes.